2009
DOI: 10.1007/978-3-642-00599-2_94
|View full text |Cite
|
Sign up to set email alerts
|

Blind Spectral-GMM Estimation for Underdetermined Instantaneous Audio Source Separation

Abstract: Abstract. The underdetermined blind audio source separation problem is often addressed in the time-frequency domain by assuming that each time-frequency point is an independently distributed random variable. Other approaches which are not blind assume a more structured model, like the Spectral Gaussian Mixture Models (Spectral-GMMs), thus exploiting statistical diversity of audio sources in the separation process. However, in this last approach, Spectral-GMMs are supposed to be learned from some training signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…For cSCT, this assumption is replaced by that of at most two predominant sources. Both assumptions do not hold exactly for most audio data [25,26]. Thus, some of the estimated local angular spectra φ(t, f, τ ) do not represent any "true" TDOA possibly leading to poor estimation of the TDOAs.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For cSCT, this assumption is replaced by that of at most two predominant sources. Both assumptions do not hold exactly for most audio data [25,26]. Thus, some of the estimated local angular spectra φ(t, f, τ ) do not represent any "true" TDOA possibly leading to poor estimation of the TDOAs.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Several works [25,26,22,23] have shown that relaxing this assumption can be very beneficial for audio source separation. Thus, we here investigate whether such an approach could be beneficial for multi-source localization.…”
Section: Em Algorithm With Multiple Sources In Each Time-frequency Binmentioning
confidence: 99%
“…Note that this example is a difficult, real-world mixture, which involves several sources mixed in the center (bass, singing voice, certain drums) and several harmonic sources with comparable pitch range (singing voice, 11 The bass is modeled as a sum of 4 sources to facilitate initialization, since we do not know a priori its spatial direction. The drums are modeled as a sum of 4 sources for the same reason, but also because the drum track is often composed of several sources (e.g., snare, hi-hat, cymbals, etc) that can be mixed in different directions.…”
Section: ) State-of-the-artmentioning
confidence: 99%
“…Finally, in section 6, we evaluate the performance of our approach on mixtures of monophonic, polyphonic and percussive music sources and compare it to the state-of-the-art approaches. Preliminary aspects of this work were presented in [28] in the case of Spectral-GMM source model and linear instantaneous mixtures. In this paper we extend it to convolutive mixtures and to other Spectral models (Spectral-GSMM and Spectral-NMF), and we provide a more consistent experimental evaluation.…”
Section: Organization Of the Papermentioning
confidence: 99%